If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(n + -2) = 32 + 4n Reorder the terms: 8(-2 + n) = 32 + 4n (-2 * 8 + n * 8) = 32 + 4n (-16 + 8n) = 32 + 4n Solving -16 + 8n = 32 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -16 + 8n + -4n = 32 + 4n + -4n Combine like terms: 8n + -4n = 4n -16 + 4n = 32 + 4n + -4n Combine like terms: 4n + -4n = 0 -16 + 4n = 32 + 0 -16 + 4n = 32 Add '16' to each side of the equation. -16 + 16 + 4n = 32 + 16 Combine like terms: -16 + 16 = 0 0 + 4n = 32 + 16 4n = 32 + 16 Combine like terms: 32 + 16 = 48 4n = 48 Divide each side by '4'. n = 12 Simplifying n = 12
| 15*2+5*x=50 | | -52+5k=6(-8k+9) | | (16x-14y)+4(5y-3x)= | | 2x(30-10)=0 | | (x^2-7)(x+2)=0 | | .5x^6-.5x^5=0 | | X*(5/3)*X=166 | | 50-6(X)=2 | | .5x-8=1 | | 50-6(6)= | | 49-4x=13-8x | | .5x-8=17 | | 64+10x=-12(1-4x) | | .5x^5-.5x^5=0 | | 1/3x=7/8 | | -11-11v=-2(v+1) | | 850=525+.21x | | 20+4y=9y | | 5y-3x=-4 | | 49c^2-9p^2= | | 6x^2-24=7x | | -4(-5x-1)=-59+11x | | 5*20-x+76=172 | | v+8=5v-12 | | -8r-22=-5(3r-11) | | 9(q+2)-3(q+3)=9 | | x-105=6x | | .33x+7=1 | | -18-8x=-10(x+4) | | f(x)=15x^4+8x^3-18x^2+1 | | m-1=-13+3m | | 3/103/4 |